2013
DOI: 10.1590/s0103-11042013000200016
|View full text |Cite
|
Sign up to set email alerts
|

Fumicultores da zona rural de Pelotas (RS), no Brasil: exposição ocupacional e a utilização de equipamentos de proteção individual (EPI)

Abstract: RESUMO Objetivou-se identificar o conhecimento dos fumicultores frente à exposição aos riscos ocupacionais e à utilização dos equipamentos de proteção individual (EPI) durante sua atividade laboral. Estudo descritivo-exploratório, com abordagem qualitativa, utilizando entrevista semiestruturada com fumicultores do Município de Pelotas (RS). A análise temática evidenciou que os trabalhadores possuem conhecimento superficial sobre os problemas de saúde aos quais estão expostos no seu ambiente laboral. Além disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
15

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 2 publications
(2 reference statements)
2
12
0
15
Order By: Relevance
“…2 Concerning the time of tobacco cultivation, similar data pointed out that families worked in tobacco farming for over 14 years. 13 Regarding the application of pesticide products, similar percentage was found among fruit growers in the city of Bento Gonçalves, Rio Grande do Sul, of 19.4%, 26 and Maringa, Paraná, of 17.1%. 27 Regarding intoxication, studies state that tobacco growers from Santa Cruz do Sul, Rio Grande do Sul and Sombrio, Santa Catarina had been victims of episodes of acute intoxication or knew someone who suffered intoxication.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…2 Concerning the time of tobacco cultivation, similar data pointed out that families worked in tobacco farming for over 14 years. 13 Regarding the application of pesticide products, similar percentage was found among fruit growers in the city of Bento Gonçalves, Rio Grande do Sul, of 19.4%, 26 and Maringa, Paraná, of 17.1%. 27 Regarding intoxication, studies state that tobacco growers from Santa Cruz do Sul, Rio Grande do Sul and Sombrio, Santa Catarina had been victims of episodes of acute intoxication or knew someone who suffered intoxication.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, companies have a tendency to only offer protection equipment, not taking into account that it needs to be appropriate and comfortable for workers in order to be effectively used. 13 The use of pesticides has been observed in other similar studies of the same population, being 100% and 94.2% respectively. [27][28] In another study, 60% of respondents said they use pesticides in agriculture for pest control purposes, thus increasing production, and because of family tradition.…”
Section: (To Be Continued) (Continuation)mentioning
confidence: 68%
See 1 more Smart Citation
“…A study developed about tobacco farmers, in the municipality of Pelotas, Rio Grande do Sul, in 1996, points out that about 6% of respondents said they were intoxicated by the use of pesticides.18 A qualitative study in 2010 in the same city identified that PPE is little accepted by growers and that these workers use only of some of the equipment because they consider it uncomfortable. 13 In a study in São Lourenço do Sul, Rio Grande do Sul, 7% of growers reported that they had had at least one episode of pesticide poisoning in their lives, moreover, it found a linear association between the number of poisoning by pesticides and minor psychiatric disorders. 10 Studies with tobacco growers have pointed out a greater risk of developing neurobehavioral alterations that could develop into cases of depression and suicide among the group associated with the use of pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…11 Tobacco growing is an exclusively rural activity, carried out entirely manually from planting to harvesting. 13 It is characterized by intensive use of pesticides and a large number of workers are directly exposed to these chemicals during cultivation of tobacco. 10 In Brazil, according to estimate of the Association of Tobacco Growers in Brazil (AFUBRA), during the 201415 harvest, tobacco farming involved 168,530 families in 14 of the 26 federate states.…”
Section: Introductionmentioning
confidence: 99%